Existence of Periodic Solutions to Nonlinear Differential Equations of Third Order with Multiple Deviating Arguments - Cemil Tunç (International Journal of Differential Equations)
We establish certain new sufficient conditions which guarantee the existence of periodic solutions for a nonlinear differential equation of the third order with multiple deviating arguments. Using the Lyapunov functional approach, we prove a specific theorem and provide an example to illustrate the theoretical analysis in this work and the effectiveness of the method utilized here.